Pluronic® P123-coated liposomal codelivery of paclitaxel and lapatinib enhances therapeutic potential via tumor cell targeting and overcoming multidrug resistance in triple-negative breast cancer cells - Subrahmanyam Pitchika, Suvendu Kumar Sahoo (Journal of Applied Pharmaceutical Science, 2023)
Clinical trials have shown that adjuvant therapy improves antitumor outcomes. The likelihood of simultaneous delivery via combination therapy may be limited by clinical complications such as pharmacokinetics and pharmacodynamics. Multidrug resistance (MDR) is a major challenge in the treatment of triple-negative breast cancers (TNBC) that lack expression of three key receptors, estrogen receptor, progesterone receptor, and human epidermal growth factor receptor 2. Our investigation revealed that no single study had examined the co-delivery of lapatinib (LPB) and paclitaxel (PTX) in TNBC to overcome MDR. So, our study aimed to develop a liposomal system coated with Pluronic® P123 to deliver PTX and LPB. The prepared PTX and LPB dual-loaded Pluronic® P123 coated liposomes (PTX/LPB-PLps) exhibited optimal size, zeta potential, and homogenous size distribution, and transmission electron microscope imaging confirmed their spherical shape. Results revealed that coating over Lps enhanced both % drug loading and encapsulation. Hydrodynamic and serum stability results supported a stable size distribution of preparations. Furthermore, cellular uptake and cytotoxic abilities against triple-negative breast cancer MDA-MB 231 cells revealed superior effects of dual-loaded PTX/LPB-PLps over single-loaded PTX or LPB Lps and uncoated dual-loaded PTX/ LPB-Lps, which is primarily because of coating lead to significantly higher intracellular levels. PTX/LPB-PLps of this design exerted an excellent synergistic effect on both MDA-MB 231 and MDA-MB 231/PTX cells, resulting in significantly improved cell inhibition with 88.57% ± 5.27% and 85.33% ± 5.11%, respectively, via circumventing multidrug-resistant protein-1-mediated PTX resistance. Evidently, the Pluronic® P123 coated liposome-based delivery mechanism is a viable nano-platform for the codelivery of PTX/LPB combination in cancer chemotherapy.